Enhancing Security Protocol For Voip Communication Using Modified Vector Quantization - Jaafar, Mohd Yazid Mohd (2013)
VoIP has introduced a new set of challenge that practically unheard off when a landline phone was used. Session Initiation Protocol (SIP) is often used as the main signaling protocol in VoIP. However, the lack of security feature has exposed SIP to a number of network threats. Public Key Infrastructure (PKI) is widely used to provide the authentication layer, but incurs maintenance cost. Verbal authentication is a security protocol specifically developed for VoIP. Unfortunately, user needs to manually perform the authentication steps over the phone. This study proposed a security protocol for video call in VoIP that does not relies on PKI. It uses image metric to secure the public key. The protocol is a certificate-less and uses human intelligence in authenticating the caller. User does not need to speak and compare the authentication code manually. Modified Vector Quantization (MVQ) and Image Metric Generation Function (IGF) are also introduced to help increase the reliability of the security protocol against network issues. The experimental results have demonstrated that the proposed protocol is robust, reliable and practical for video call in VoIP communication. The security analysis also has proved that the proposed protocol can resist known attacks against VoIP communication.